How Generative AI Improves Supply Chain Management - Menache, Ishai; Pathuri, Jeevan; Simchi-Levi, David; Linton, Tom (Harvard Business Review, 2025)
Companies face a variety of complex challenges in designing and optimizing their supply chains. Increasing their resilience, reducing costs, and improving the quality of their planning are just a few of them. Over the past few decades, advances in information technologies have allowed firms to move from decision-making on the basis of intuition and experience to more automated and data-driven methods. As a result, businesses have seen efficiency gains, substantial cost reductions, and improved customer service.